What can be learned from a Knowledge-intensive System? - Agus Gunawan; Mohamed A. Wahdan; H. Jaap van den Herik; Yoke Pribadi Kornarius (Jurnal Administrasi Bisnis, 2011)
The paper aims at describing what can be learned from a Knowledge-intensive Sys-tem (KIS) by a manager of an Indonesian SME Garment Manufacturer (ISGM).For this purpose, we use the system LIA (Leading to Information Access). LIA isa system that (1) handles financial related transactions, (2) processes them accordingto Indonesian accounting standard procedures, and (3) gives the interpretation of theprocess results to the financial analysis. By learning from the interpretation of thecompany’s historical data, an owner’s understanding of critical financial factors ingarment industry may increase and let the company flourish.Keywords: Knowledge-intensive System, Financial Analysis, Learning Process,Indonesia SME Garment Manufacturers, Business Administration